Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.